(untitled) (KYAMC Journal, 2022)
Background: Somatoform and dissociative disorder categories have emerged from a common root, there was no apparent anatomical and physiological basis and which had a temporal relationship to a precipitating event. Objectives: To evaluate and compare of stressful life events of the patients of somatoform disorders and dissociative disorders. Materials and methods: This was a comparative cross-sectional study carried out in the outpatient department of Psychiatry, Khwaja Yunus Ali Medical College, Sirajganj. The study populations were 100 somatoform disorder and 100 dissociative disorder patients. Data were collected by pre-designed data collection sheet. Then data were edited, cleaned and analyzed. Results: Stressful life events were observed to be significantly more frequent in both the groups. Family conflicts (29%) and sexual problem (16%) were more common in the somatoform disorder group of patients but marital conflict (26%) and death of the close family member (11%) were more common in the dissociative disorder group of patients. This study shows that dissociative disorder patients were observed to experience a variety of life events more than somatoform disorder group of patients. Conclusion: The stressful life events were reported more in dissociative disorder. The results suggest a substantial involvement of stressful life events in genesis of somatoform disorders and dissociative disorders, although no significant difference is noticed. KYAMC Journal Vol. 13, No. 02, July 2022: 63-65